Pelatihan Model Pembelajaran Project Citizen Bagi Guru-Guru di Sekolah Indonesia Johor Bahru, Malaysia Untuk Meningkatkan Civic Literacy - Srie Mulyani; Tiara Yogiarni; Jennyta Caturiasari; D Wahyudin; Eko Wahyunanto Prihono (Universitas Pendidikan Indonesia Kampus Purwakarta, 2023)
Technology has become a new tool that can help in all aspects of life; today, technology helps develop educational facilities to be more effective and efficient. The progress of civilization in technology means that the world of education must be more prepared and skilled in facing global challenges. Skills that are important to develop, based on the National Education Association (NEA) recommends the importance of developing the Four Cs, namely (1) Critical thinking and problem solving, (2) Communication, (3) Collaboration, and (4) Creativity and Innovation. Problem-solving is the main reference in the educational process, especially in Pancasila and Citizenship Education (PPKn). This can be seen from PPKn learning, which is still dominated by conventional systems, so the application of PPKn learning, which is oriented to contextual multiple intelligences, is still far from expectations. An adaptive model that can improve PPKn skills and learning outcomes is by using Citizenship Learning Practices (project citizenship). Therefore, elementary school teachers need to have the skills to develop and implement learning with project citizenship. Project Citizenship was developed from a critical or reflective thinking approach model. The learning approach recommended to be developed is oriented towards critical thinking and problem-solving. Through project citizen training, which is applied in the teaching and learning process, it is hoped that students will be able to familiarize themselves with carrying out the inquiry process, which is believed to make learning more meaningful.